2011
DOI: 10.1364/boe.2.000600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bile absorption coefficients on the estimation of liver tissue optical properties and related implications in discriminating healthy and tumorous samples

Abstract: We investigated differences between healthy tissue and metastatic tumor from ex vivo human partial liver resections using diffuse optical spectroscopy with a fiber optic probe. We extracted various physiological and morphological parameters from the spectra. During evaluation of the residual between the measurements and a fit model based on diffusion theory, we found that bile is an additional chromophore absorbing in the visible wavelength range that was missing in our model. Consistency of the residual with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 38 publications
(60 reference statements)
10
113
1
Order By: Relevance
“…3 suggest that the optical properties of tissue types contain the most discriminative information for tissue classification in the VIS wavelength range between 450 nm and 750 nm. These findings are similar to those that have been reported for different ex vivo studies on human liver tissue of tumor patients with primary cancer [14], as well as with liver metastases [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…3 suggest that the optical properties of tissue types contain the most discriminative information for tissue classification in the VIS wavelength range between 450 nm and 750 nm. These findings are similar to those that have been reported for different ex vivo studies on human liver tissue of tumor patients with primary cancer [14], as well as with liver metastases [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…These observations originate from different chromophores for both primary and secondary tumor types. Since metastases consist of abnormal cells with their origin in other organs, the amount of bile with high absorption between 400 nm and 500 nm is low [17,18,31]. Extracted from diffuse reflectance spectra, Nachabé et al [18] have shown that the amount of bile in metastatic tumor tissues is 80% lower than in healthy liver tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations